Self-Management and Self-Efficacy In Hemodialysis Patients - agavia kristi purba; Etika Emaliyawati; Aat Sriati (Journal of Nursing Care, 2018)
Introduction, the success of treatment in chronic renal failure patients with hemodialysis required the existence of self-management and self-efficacy. Previous studies showed that self-efficacy had the influence to bring up self-management behavior. The purpose of this study was to determine patients’ self-management and self-efficacy in chronic renal failure patients who had hemodialysis at Advent’s Hospital Bandung. Methods, this study was a quantitative descriptive research.  The study samples were chosen using consecutive sampling technique. The number of samples was 75 patients. Data were collected using the SMBQ and PEPPI+Life Options DeNovo instruments. Data were analyzed using the quantitative descriptive approach with mean value and frequency distribution. The results of self-efficacy in patients with chronic renal failure with hemodialysis was   high (54.7%) and the self-management behavior was in a good category (53.3%). The conclusion of this study is that the patient has a good self-management as well as self-efficacy.  However, this study found the poor category of the partnership in caring aspect. Recommendation There is a need for a strategy to improve the self-management in the partnership in caring aspect by providing emotional support, educating patients related to treatment and care, and evaluating patients’ health development periodically.